2006
DOI: 10.1093/annonc/mdj040
|View full text |Cite
|
Sign up to set email alerts
|

Influence of thyroid hormone receptors on breast cancer cell proliferation

Abstract: The results of this study reveal substantial changes in the expression profile of thyroid hormone receptors suggesting a possible deregulation that could trigger breast cancer development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
67
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(72 citation statements)
references
References 18 publications
3
67
0
2
Order By: Relevance
“…Previous studies described TR␣ as located in the nuclei of epithelial cells from normal breast ducts and acini, whereas in breast cancer cells such receptors are located in the cytoplasm (8). Moreover, TR␤ presented a nuclear location in benign proliferative diseases and carcinomas in situ and a cytoplasmic location in normal breast and infiltrative carcinomas (8).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Previous studies described TR␣ as located in the nuclei of epithelial cells from normal breast ducts and acini, whereas in breast cancer cells such receptors are located in the cytoplasm (8). Moreover, TR␤ presented a nuclear location in benign proliferative diseases and carcinomas in situ and a cytoplasmic location in normal breast and infiltrative carcinomas (8).…”
Section: Discussionmentioning
confidence: 96%
“…No difference was evident in the localization of THRs in BDL cholangiocytes after T3 administration. The change in cell localization of THRs in normal mammary epithelial cells with respect to pathological conditions has been described (8). Previous studies described TR␣ as located in the nuclei of epithelial cells from normal breast ducts and acini, whereas in breast cancer cells such receptors are located in the cytoplasm (8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental studies have shown that THs influence both the differentiation of normal breast cells [44] and the proliferation of BC cells [44,50,51] . The proliferative effect of T3 has been demonstrated in various types of cancer.…”
Section: Cancermentioning
confidence: 99%
“…Thyroid hormone receptors affect both the normal breast cell differentiation and breast cancer cell proliferation, with effects of thyroid hormones similar to those caused by estrogens. 2,3 Some studies have indicated thyroid autoimmune changes as prognostic factors in breast cancer. 4 Relationship between thyroid diseases with breast cancer was demonstrated in several studies.…”
Section: Introductionmentioning
confidence: 99%